The quality of life after cardiac surgery in octogenarians and evaluation of its early and mid-term results - AYDIN, CEMALETTİN; Kara, Ibrahim; Ay, Yasin; Koksal, Cengiz; AYDIN, CEMALETTİN; Yanartas, Mehmet; Yildirim, Tekin (My University, 2012)
Objective: The aim of this study is to evaluate our early and mid- term results and the qualities of life of the patients aged eighty years or older who underwent heart surgery.
Keywords: surgery